Formulasi dan Karakterisasi Sediaan Nanoemulgel Serbuk Lidah Buaya (Aloe Vera L.) - Teguh Imanto; Roseh Prasetiawan; Erindyah Retno Wikantyasning (Universitas Muhammadiyah Surakarta, 2019)
Aloe vera L. contains antiseptic saponins and anthraquinone complexes as antibacterial. This research was conducted to formulate aloe vera powder into nanoemulgel, characterize and test its physical properties, and to know the effect of gelling agent concentration (carbopol and chitosan) on nanoemulgel. Emulsion type used is oil in water (O / W) with surfactant tween 80 and co-surfactant propylene glycol. Nanoemulsion is characterized by percent of transmittance with UV-Vis spectrophotometer, also potential droplet and zeta size distribution with Particle Size Analyzer. Hydrogels consist of 4 combination formulas of carbopol 0.5%; 1%; 1.5%; 2% and 0.3% chitosan. The formula is tested for physical properties including organoleptic, pH, spreadability, adhesion, viscosity and stability with freeze thaw method. The results showed that the nanoemulsion droplet size was 65.05nm ± 13.49 with zeta potential of -0.1mV and the percent of transmittance above 98%. The result of physical properties of the four formulas shows that the different gelling agent concentration gives different physical properties of viscosity and spreadability. Overall, formula 3 has the best physical properties and physical stability compared to formula 1, 2 and 4.